1999
DOI: 10.1002/(sici)1097-0142(19990315)85:6<1389::aid-cncr24>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinting of H19 and insulin‐like growth factor‐2 in pediatric germ cell tumors

Abstract: These data suggest that LOI at H19 and IGF2 also may be common in pediatric testicular GCTs. However, ovarian and extragonadal pediatric GCTs showed variable patterns of LOI that may indicate differences in the timing of carcinogenesis in germ cells at these sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…The consistent expression of both parental alleles of the H19 and IGF2 genes implies that TGCTs may develop from precursor cells that have either erased their imprint or been subjected to a relaxation of the normal monoallelic expression of these genes ensuing from demethylation at the imprinted allele (van Gurp et al, 1994). This is consistent with the finding of Ross and colleagues who also demonstrated loss of imprinting (LOI) of H19 and IGF-2 genes in both pediatric and TYA GCTs (Ross et al, 1999). Their results suggested that while LOI of H19 and IGF-2 may be common in pediatric and TYA TGCTs, there was a variable pattern of LOI in ovarian GCTs in these age groups, which was proposed to reflect the stage of imprinting during germ cell development at which tumorigenesis occurred.…”
Section: Genomic Imprintingsupporting
confidence: 82%
See 2 more Smart Citations
“…The consistent expression of both parental alleles of the H19 and IGF2 genes implies that TGCTs may develop from precursor cells that have either erased their imprint or been subjected to a relaxation of the normal monoallelic expression of these genes ensuing from demethylation at the imprinted allele (van Gurp et al, 1994). This is consistent with the finding of Ross and colleagues who also demonstrated loss of imprinting (LOI) of H19 and IGF-2 genes in both pediatric and TYA GCTs (Ross et al, 1999). Their results suggested that while LOI of H19 and IGF-2 may be common in pediatric and TYA TGCTs, there was a variable pattern of LOI in ovarian GCTs in these age groups, which was proposed to reflect the stage of imprinting during germ cell development at which tumorigenesis occurred.…”
Section: Genomic Imprintingsupporting
confidence: 82%
“…When compared with adult TGCTs, the frequency of LOI was lower in pediatric testicular and extragonadal GCTs and in TYA ovarian GCTs. As such, LOI of H19 and IGF-2 has been found in the pediatric, TYA and older adult populations although LOI patterns varied across the three populations (van Gurp et al, 1994;Nonomura et al, 1997;Ross et al, 1999;Schneider et al, 2001). Although this suggests that these tumors all arise from PGCs, this may nevertheless occur at different stages of germ cell development.…”
Section: Genomic Imprintingmentioning
confidence: 97%
See 1 more Smart Citation
“…At present, the various histological sub-entities of GCTs at all sites and of all age groups are grouped together in keeping with the theoretical concept by Teilum that all subtypes share a common cell of origin, the totipotent primordial germ cell (PGC) [1]. Recently, this hypothesis has received strong experimental support as several studies of imprinting status in GCTs have revealed that an imprinting pattern characteristic of PGCs-although at different stages of development-can be detected in GCTs of various histologies, both at gonadal and non-gonadal sites [2,3,37,38]. Given the common cellular origin of GCTs [2], the question arises regarding the biologic mechanisms behind the clinical, histologic, and genetic heterogeneity that is seen.…”
Section: Common Histogenesis But Heterogeneity Of Gctsmentioning
confidence: 67%
“…Current methods for evaluating allele-specific expression have a number of limitations. PCR followed by restriction endonuclease digestion is a traditional method, 5,6 but the efficiency of restriction endonucleases is incomplete. Mispaired heteroduplex DNA is commonly formed during PCR amplification and cannot be cleaved, resulting in allelic skewing.…”
Section: Introductionmentioning
confidence: 99%